2010
DOI: 10.4049/jimmunol.0902501
|View full text |Cite
|
Sign up to set email alerts
|

Production of Vascular Endothelial Growth Factors from Human Lung Macrophages Induced by Group IIA and Group X Secreted Phospholipases A2

Abstract: Angiogenesis and lymphangiogenesis mediated by vascular endothelial growth factors (VEGFs) are main features of chronic inflammation and tumors. Secreted phospholipases A2 (sPLA2s) are overexpressed in inflammatory lung diseases and cancer and they activate inflammatory cells by enzymatic and receptor-mediated mechanisms. We investigated the effect of sPLA2s on the production of VEGFs from human macrophages purified from the lung tissue of patients undergoing thoracic surgery. Primary macrophages express VEGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
90
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 64 publications
(137 reference statements)
4
90
0
3
Order By: Relevance
“…A normal tissue microenvironment can suppress malignancy, while certain pathogenetic tissue features are critical for tumor development. 63,54 A myriad of immune cells are present in the TC microenvironment and in some cases are associated with patient outcome. 66,68 However, only studies assessing the functional role of TAMs and TAMCs in the TC microenvironment have provided evidence for their protumorigenic role.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A normal tissue microenvironment can suppress malignancy, while certain pathogenetic tissue features are critical for tumor development. 63,54 A myriad of immune cells are present in the TC microenvironment and in some cases are associated with patient outcome. 66,68 However, only studies assessing the functional role of TAMs and TAMCs in the TC microenvironment have provided evidence for their protumorigenic role.…”
Section: Discussionmentioning
confidence: 99%
“…TC cells, TAMs, TAMCs and other immune cells are a major source of proangiogenic and lymphangiogenic molecules. 53,54 Interestingly, immune cells and tumors can produce pro-and anti-angiogenic isoforms of VEGFs. 62 A deeper knowledge of the balance between these isoforms could lead to the discovery of novel targets that can be manipulated to block TC growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated that myeloid cells produce various angiogenic factors including vascular endothelial growth factor (VEGF) (2), interleukin 8 (IL-8) (3), basic fibroblast growth factor (bFGF) (4), and Bv8 (5).…”
mentioning
confidence: 99%
“…The sPLA2 group IIA was initially detected in synovial fluid of patients with rheumatoid arthritis 15,16 . Several studies demonstrated that the sPLA2 group IIA was involved in inflammatory process [17][18][19] and many phospholipases A2 inhibitors have been discovered and their effectiveness have been proved as a treatment of inflammatory diseases [20][21][22] . Because overproduction of these inflammatory mediators might cause inflammatory damage, we focused in the present study on the evaluation of the anti-inflammatory effect of LEJ extracts by measuring the inhibition of the pro-inflammatory sPLA2 group IIA as well as their antioxidant activity.…”
mentioning
confidence: 99%